Determination of Antioxidant 264 in the Butyl Rubber Stopper and the Compatibility with Recombinant Potent Antitumor and Antivirus Protein Injection - Min Zhao; Xianhui Li; Di Zhang; Longshan Zhao (Journal of Analytical Methods in Chemistry)
Objective. To establish a method for extraction and determination of antioxidant 264 (2,6-di-tert-butyl-4-methylphenol) in the brominated butyl rubber stopper for injection and migration study in recombinant potent antitumor and antivirus protein injection (Novaferon). Methods. Dichloromethane-ethanol was adopted as the extraction solvent during the process of reflux extraction of antioxidant 264 in the brominated butyl rubber stopper. High-performance liquid chromatography (HPLC) was used for the determination of the migration of antioxidant 264 to Novaferon. The mobile phase consisted of acetonitrile-water (80 : 20, v/v). The flow rate was 1.5 mL/min. The detection wavelength was 280 nm. Results. The linearity range was from 4.003 to 200.150 μg/mL (r2 = 0.99996), and the average recovery of antioxidant 264 was 97.8%. The applicability of the methodology was good, which can be used for the determination of antioxidant 264. The results indicated that antioxidant 264 was not detected in Novaferon after the accelerated test and three months of long-term test. Conclusion. The established validated method in this study can be used for the determination of antioxidant 264 in the rubber stopper, and the brominated butyl rubber stopper has good compatibility with Novaferon.